2019
DOI: 10.1371/journal.pone.0225058
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical medical student reflections on implicit bias: Implications for learning and teaching

Abstract: ContextImplicit bias affects health professionals’ clinical decision-making; nevertheless, published reports of medical education curricula exploring this concept have been limited. This research documents a recent approach to teaching implicit bias.MethodsMedical students matriculating during 2014 and 2015 participated in a determinants of health course including instruction about implicit bias. Each submitted a reflective essay discussing implicit bias, the experience of taking the Implicit Association Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…19 Studies have also demonstrated that students believe implicit bias education should occur in pre-clinical, didactic years, prior to exposure to patient care arenas. 20 Didactic instruction about bias may be the initial step for a learner in recognizing biases. Colleges can begin by supplementing cultural competency curriculums with implicit bias focuses.…”
Section: Tools To Address Implicit Bias Educational Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Studies have also demonstrated that students believe implicit bias education should occur in pre-clinical, didactic years, prior to exposure to patient care arenas. 20 Didactic instruction about bias may be the initial step for a learner in recognizing biases. Colleges can begin by supplementing cultural competency curriculums with implicit bias focuses.…”
Section: Tools To Address Implicit Bias Educational Interventionsmentioning
confidence: 99%
“…When given in conjunction with the IAT, students reported newfound insight into unperceived biases, providing them the tools to be more perceptive in the future. 9,20 Prior to initiating reflection, educators must explain the "why" behind reflecting, so students understand the motivation for self-reflection. Educators must be skillfully trained, must cultivate a safe space for students to face these unconscious perceptions and feedback delivery should be considered when assessing.…”
Section: Reflectionmentioning
confidence: 99%
“…1 Unconscious biases are universal and have adverse consequences for the workplace, health care, and the learning environment. [2][3][4] Studies show that clinicians' negative implicit bias correlated with poorer quality of care, inadequate clinician-patient communication, and health care disparities and inequities. [3][4][5][6][7][8] Unconscious biases adversely affect faculty recruitment and promotion, including the persistent underrepresentation of Black Americans and other minorities in medicine, further exacerbating racial health care disparities.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Authors of the IATs have noted that the tool may not reflect actual biases or acts of discrimination related to identified preferences. 4 Subsequently, the objective of this study was to determine: (1) if a brief educational workshop can increase knowledge and perceptions regarding unconscious bias, and (2) show that inaccurate first impressions can be elicited without the IATs.…”
Section: Introductionmentioning
confidence: 99%
“…experience and information that we gather early in life and are made more complex because they intersect with our culture and identity. Critical reflection allows us to identify and acknowledge both explicit and implicit (unknown or hidden) bias, [10] and is an important step in becoming more culturally competent. [2,11] Cultural competence may be especially important for training students in global electronics sustainability due to the global nature of the electronics supply chain and associated waste (ewaste).…”
Section: Relevant Literature Review and Backgroundmentioning
confidence: 99%